The physical activity at work (PAW) study protocol: a cluster randomised trial of a multicomponent short-break intervention to reduce sitting time and increase physical activity among office workers in Thailand - Chen Huijun,Cynthia (Springer Science and Business Media LLC, 2020)
10.1186/s12889-020-09427-5